Pelatihan Fotografi Produk Pada Kelompok Masyarakat Desa Rempoah, Kabupaten Banyumas - Miranti, Adita; Nasrul Majid, M.Rafiun; Sudiana, Yudi (Universitas katolik Musi Charitas, 2022)
The rapid development of internet media, makes people are required to be more creative and innovative in using internet media and designing their product promotion designs, in this case visual designs in the form of product photos that are quite interesting and creative. This is due to the emergence of competition that emphasizes creativity and innovation in promotional and marketing activities for the public using the internet as a means to carry out their promotional, marketing and transaction activities. This ability is still very low for members of community groups, especially community groups in Rempoah Village, Banyumas Regency. This is what motivates the community activity implementation team to provide “Design Photography” training using existing, affordable and easy-to-obtain equipment and produce product photos that match their needs in carrying out promotions. This training is carried out by providing theoretical material, followed by direct field practice, where participants apply the knowledge related to product photography that has been conveyed previously. From this training, participants gain new knowledge on how to make attractive product photos using the tools they already have. The rapid development of internet media, makes people are required to be more creative and innovative in using internet media and designing their product promotion designs, in this case visual designs in the form of product photos that are quite interesting and creative. This is due to the emergence of competition that emphasizes creativity and innovation in promotional and marketing activities for the public using the internet as a means to carry out their promotional, marketing and transaction activities. This ability is still very low for members of community groups, especially community groups in Rempoah Village, Banyumas Regency. This is what motivates the community activity implementation team to provide “Design Photography” training using existing, affordable and easy-to-obtain equipment and produce product photos that match their needs in carrying out promotions. This training is carried out by providing theoretical material, followed by direct field practice, where participants apply the knowledge related to product photography that has been conveyed previously. From this training, participants gain new knowledge on how to make attractive product photos using the tools they already have. Keywords : Product photography, Promotion, Community Group